Polycarbonate resin composition and molded article made therefrom
The polycarbonate resin composition, combining a copolymer polycarbonate resin with an aromatic polycarbonate resin, addresses the limitations of conventional polycarbonate resins by providing enhanced heat resistance, transparency, scratch resistance, and impact resistance, suitable for various applications including interior automobile parts.
Patent Information
- Application Number
- JP2023147279
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-12
- Publication Date
- 2025-03-25
AI Technical Summary
Conventional polycarbonate resins lack excellent heat resistance, transparency, scratch resistance, and impact resistance, particularly when not coated, which limits their applications in various fields.
A polycarbonate resin composition is developed, comprising a copolymer polycarbonate resin with a specific structure and an aromatic polycarbonate resin, specifically formulated to enhance heat resistance, transparency, scratch resistance, and impact resistance.
The polycarbonate resin composition achieves excellent heat resistance, transparency, scratch resistance, and impact resistance, making it suitable for use in interior automobile parts and other applications without the need for additional coatings.
Smart Images

Figure 2025040458000001 
Figure 2025040458000002 
Figure 2025040458000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a polycarbonate resin composition having excellent heat resistance, transparency, scratch resistance and impact resistance, and to a molded article made of the same. [Background technology]
[0002] Conventionally, methacrylic resins, polycarbonate resins (hereinafter sometimes referred to as PC), etc. are known as transparent resins, and these resins are used in a wide range of fields such as electrical and electronic components, optical components, automotive components, and mechanical components in the form of molded products, films, sheets, etc.
[0003] Methacrylic acid resins such as polymethyl methacrylate (hereinafter sometimes referred to as PMMA) have high transparency and high surface hardness (pencil hardness H to 3H), and are widely used as optical materials such as lenses and optical fibers. However, their glass transition temperature is low at about 100°C, and their heat resistance is poor, limiting their use in fields requiring heat resistance. Another problem is that they have low impact resistance.
[0004] Polycarbonate resin made from bisphenol A has excellent transparency, impact resistance, heat resistance, and dimensional stability, and is therefore used as an engineering plastic in a wide range of fields, including the housings of electrical and electronic devices, interior and exterior parts of automobiles, building materials, furniture, musical instruments, miscellaneous goods, etc. Furthermore, compared to inorganic glass, it has a lower specific gravity, making it possible to reduce weight and offering excellent productivity, and therefore is used for windows in automobiles, etc. Furthermore, sheets and films using polycarbonate resins are widely used as various display devices and protective parts for automobile interiors by subjecting them to additional secondary processing such as coating, lamination, and surface modification.
[0005] However, when uncoated polycarbonate resin is measured in accordance with JIS K5600-5-4, General test methods for paints - Part 5: Mechanical properties of coatings - Section 4: Scratch hardness (pencil method), the pencil hardness is only about 2B, which is an issue for a paint-less material in that the surface is easily scratched.
[0006] Therefore, it is known to use copolymerized polycarbonate resins with high surface hardness. Also, a method of producing polycarbonates or copolycarbonates with 2,2-bis(4-hydroxy-3-methylphenyl)propane as a repeating unit has been described. Although the polycarbonate resins have improved surface hardness, they have a problem in that they are inferior in heat resistance and impact resistance compared to polycarbonate resins (Patent Documents 1 to 6).
[0007] Therefore, an object of the present invention is to solve such problems and to provide a polycarbonate resin composition excellent in heat resistance, transparency, scratch resistance and impact resistance, and a molded article made from the same. [Prior art documents] [Patent documents]
[0008] [Patent Document 1] Patent No. 5173803 [Patent Document 2] Japanese Patent Application Publication No. 64-069625 [Patent Document 3] Japanese Patent Application Publication No. 08-183852 [Patent Document 4] Japanese Patent Application Publication No. 08-034846 [Patent Document 5] JP 2002-117580 A [Patent Document 6] Patent No. 3768903 Summary of the Invention [Problem to be solved by the invention]
[0009] An object of the present invention is to provide a polycarbonate resin composition having excellent heat resistance, transparency, scratch resistance and impact resistance, and a molded article made from the same. [Means for solving the problem]
[0010] As a result of intensive research conducted by the present inventors in order to achieve this object, they discovered that a resin composition containing a copolymer polycarbonate resin having a specific structure and an aromatic polycarbonate resin can solve the above problems, and arrived at the present invention. That is, the present invention is as follows:
[0011] 1. A polycarbonate resin composition comprising 1 to 99 parts by weight (component A) of a copolymeric polycarbonate resin having a content of repeating units (a) represented by the following formula (1) of 5 to 95 mol % and a content of repeating units (b) represented by the following formula (2) of 95 to 5 mol % relative to the total repeating units, and 99 to 1 part by weight of an aromatic polycarbonate resin (component B).
[0012] [ka]
[0013] (In the above formula (1), ring Z is a naphthalene ring, R 1 and R 2 each independently represents at least one group selected from the group consisting of a hydrogen atom, a halogen atom, an alkyl group having 1 to 18 carbon atoms, an alkoxy group having 1 to 18 carbon atoms, a cycloalkyl group having 6 to 20 carbon atoms, a cycloalkoxy group having 6 to 20 carbon atoms, an alkenyl group having 2 to 10 carbon atoms, an aryl group having 6 to 14 carbon atoms, an aryloxy group having 6 to 14 carbon atoms, an aralkyl group having 7 to 20 carbon atoms, an aralkyloxy group having 7 to 20 carbon atoms, a nitro group, an aldehyde group, a cyano group, and a carboxyl group.
[0014] [ka]
[0015] (In the above formula (2), R 3 and R 4 each independently represents at least one group selected from the group consisting of a hydrogen atom, a halogen atom, an alkyl group having 1 to 18 carbon atoms, an alkoxy group having 1 to 18 carbon atoms, a cycloalkyl group having 6 to 20 carbon atoms, a cycloalkoxy group having 6 to 20 carbon atoms, an alkenyl group having 2 to 10 carbon atoms, an aryl group having 6 to 14 carbon atoms, an aryloxy group having 6 to 14 carbon atoms, an aralkyl group having 7 to 20 carbon atoms, an aralkyloxy group having 7 to 20 carbon atoms, a nitro group, an aldehyde group, a cyano group, and a carboxyl group, and when there are a plurality of each of these groups, they may be the same or different, e and f each represent an integer of 1 to 4, and W represents a single bond or at least one group selected from the group consisting of groups represented by the following formula (3):
[0016] [ka]
[0017] (In the above formula (3), R 5 ,R 6 ,R 7 ,R 8 ,R 9 ,R 10 ,R 11 and R 12 each independently represents at least one group selected from the group consisting of a hydrogen atom, an alkyl group having 1 to 18 carbon atoms, an aryl group having 6 to 14 carbon atoms, and an aralkyl group having 7 to 20 carbon atoms, and when there are a plurality of groups, they may be the same or different; R 13 and R 14each independently represents at least one group selected from the group consisting of a hydrogen atom, a halogen atom, an alkyl group having 1 to 18 carbon atoms, an alkoxy group having 1 to 18 carbon atoms, a cycloalkyl group having 6 to 20 carbon atoms, a cycloalkoxy group having 6 to 20 carbon atoms, an alkenyl group having 2 to 10 carbon atoms, an aryl group having 6 to 14 carbon atoms, an aryloxy group having 6 to 14 carbon atoms, an aralkyl group having 7 to 20 carbon atoms, an aralkyloxy group having 7 to 20 carbon atoms, a nitro group, an aldehyde group, a cyano group, and a carboxyl group; R 15 ,R 16 ,R 17 and R 18 each independently represents at least one group selected from the group consisting of an alkyl group having 1 to 18 carbon atoms, a cycloalkyl group having 6 to 20 carbon atoms, an alkenyl group having 2 to 10 carbon atoms, an aryl group having 6 to 14 carbon atoms, and an aralkyl group having 7 to 20 carbon atoms, and when there are a plurality of groups, they may be the same or different, c is an integer of 1 to 10, d is an integer of 4 to 7, h and i are integers of 1 to 3, and g is an integer of 1 to 100.
[0018] 2. The polycarbonate resin composition according to item 1 above, wherein the aromatic polycarbonate resin (component B) is an aromatic polycarbonate resin containing a repeating unit derived from bisphenol A. 3. The polycarbonate resin composition according to item 1 or 2 above, which has a single glass transition temperature. 4. The polycarbonate resin composition according to any one of items 1 to 3 above, which has a glass transition temperature of 100 to 300°C. 5. Indentation hardness measured according to ISO / TS 19278 is 150-400 (N / mm 2 5. The polycarbonate resin composition according to any one of items 1 to 4 above, wherein 6. The polycarbonate resin composition according to any one of items 1 to 5 above, which has a pencil hardness of H or more as measured in accordance with JIS K5600. 7. The polycarbonate resin composition according to any one of items 1 to 6 above, wherein a test piece having a thickness of 7.2 mm has a total light transmittance of 85% or more. 8. Notched Charpy impact value is 3kJ / m 28. The polycarbonate resin composition according to any one of items 1 to 7 above. 9. A molded article obtained by injection molding the polycarbonate resin composition according to any one of items 1 to 8 above. 10. A sheet or film obtained by extrusion molding the polycarbonate resin composition according to any one of items 1 to 8 above. Effect of the Invention
[0019] The polycarbonate resin composition of the present invention and the molded article made of the same are excellent in heat resistance, transparency, scratch resistance and impact resistance, and therefore can be suitably used for automobile interior parts, and therefore the industrial effects thereof are exceptional. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0020] The present invention will be described in detail below.
[0021] <Copolymer polycarbonate resin (Component A)> The polycarbonate resin composition of the present invention is a polycarbonate resin composition containing 1 to 99 parts by weight (component A) of a copolymeric polycarbonate resin having a content of repeating units (a) represented by the following formula (1) of 5 to 95 mol % and a content of repeating units (b) represented by the following formula (2) of 95 to 5 mol % relative to all repeating units, and 99 to 1 part by weight of an aromatic polycarbonate resin (component B).
[0022] [ka]
[0023] (In the above formula (1), ring Z is a naphthalene ring, R 1 and R 2each independently represents at least one group selected from the group consisting of a hydrogen atom, a halogen atom, an alkyl group having 1 to 18 carbon atoms, an alkoxy group having 1 to 18 carbon atoms, a cycloalkyl group having 6 to 20 carbon atoms, a cycloalkoxy group having 6 to 20 carbon atoms, an alkenyl group having 2 to 10 carbon atoms, an aryl group having 6 to 14 carbon atoms, an aryloxy group having 6 to 14 carbon atoms, an aralkyl group having 7 to 20 carbon atoms, an aralkyloxy group having 7 to 20 carbon atoms, a nitro group, an aldehyde group, a cyano group, and a carboxyl group.
[0024] [ka]
[0025] (In the above formula (2), R 3 and R 4 each independently represents at least one group selected from the group consisting of a hydrogen atom, a halogen atom, an alkyl group having 1 to 18 carbon atoms, an alkoxy group having 1 to 18 carbon atoms, a cycloalkyl group having 6 to 20 carbon atoms, a cycloalkoxy group having 6 to 20 carbon atoms, an alkenyl group having 2 to 10 carbon atoms, an aryl group having 6 to 14 carbon atoms, an aryloxy group having 6 to 14 carbon atoms, an aralkyl group having 7 to 20 carbon atoms, an aralkyloxy group having 7 to 20 carbon atoms, a nitro group, an aldehyde group, a cyano group, and a carboxyl group, and when there are a plurality of each of these groups, they may be the same or different, e and f each represent an integer of 1 to 4, and W represents a single bond or at least one group selected from the group consisting of groups represented by the following formula (3):
[0026] [ka]
[0027] (In the above formula (3), R 5 ,R 6 ,R 7 ,R 8 ,R 9 ,R 10 ,R 11 and R 12each independently represents at least one group selected from the group consisting of a hydrogen atom, an alkyl group having 1 to 18 carbon atoms, an aryl group having 6 to 14 carbon atoms, and an aralkyl group having 7 to 20 carbon atoms, and when there are a plurality of groups, they may be the same or different; R 13 and R 14 each independently represents at least one group selected from the group consisting of a hydrogen atom, a halogen atom, an alkyl group having 1 to 18 carbon atoms, an alkoxy group having 1 to 18 carbon atoms, a cycloalkyl group having 6 to 20 carbon atoms, a cycloalkoxy group having 6 to 20 carbon atoms, an alkenyl group having 2 to 10 carbon atoms, an aryl group having 6 to 14 carbon atoms, an aryloxy group having 6 to 14 carbon atoms, an aralkyl group having 7 to 20 carbon atoms, an aralkyloxy group having 7 to 20 carbon atoms, a nitro group, an aldehyde group, a cyano group, and a carboxyl group; R 15 ,R 16 ,R 17 and R 18 each independently represents at least one group selected from the group consisting of an alkyl group having 1 to 18 carbon atoms, a cycloalkyl group having 6 to 20 carbon atoms, an alkenyl group having 2 to 10 carbon atoms, an aryl group having 6 to 14 carbon atoms, and an aralkyl group having 7 to 20 carbon atoms, and when there are a plurality of groups, they may be the same or different, c is an integer of 1 to 10, d is an integer of 4 to 7, h and i are integers of 1 to 3, and g is an integer of 1 to 100.
[0028] In the formula (1), ring Z is a naphthalene ring. The two rings Z connected to the carbon atom at position 9 of the fluorene ring may be different from each other, but are usually the same in most cases. The substitution position of ring Z relative to the 9-position of the fluorene ring is not particularly limited. For example, the substitution may be at either the 1-position or the 2-position of the naphthalene ring relative to the 9-position of the fluorene ring, and substitution at the 2-position is preferred.
[0029] The substitution positions of the oxygen atom (-O-) and the ester bond [-OC(=O)-] which form a carbonate bond for linking the 9,9-bis-fused polycyclic arylfluorene skeleton are not particularly limited as long as they are positions other than the bonding position between the ring Z and the fluorene ring, and usually, they are substituted at any of the 5- to 8-positions of a naphthyl group bonded at the 1- or 2-position to the 9-position of the fluorene ring, and the 1- or 2-position of the naphthalene ring is substituted with respect to the 9-position of the fluorene ring (substitution in a 1-naphthyl or 2-naphthyl relationship), and with respect to this substitution position, substitution at the 1,5-positions or 2,6-positions is preferred, and substitution at the 2,6-positions is more preferred.
[0030] In the formula (1), R 1 and R 2 each independently represents at least one group selected from the group consisting of a hydrogen atom, a halogen atom, an alkyl group having 1 to 18 carbon atoms, an alkoxy group having 1 to 18 carbon atoms, a cycloalkyl group having 6 to 20 carbon atoms, a cycloalkoxy group having 6 to 20 carbon atoms, an alkenyl group having 2 to 10 carbon atoms, an aryl group having 6 to 14 carbon atoms, an aryloxy group having 6 to 14 carbon atoms, an aralkyl group having 7 to 20 carbon atoms, an aralkyloxy group having 7 to 20 carbon atoms, a nitro group, an aldehyde group, a cyano group, and a carboxyl group.
[0031] Examples of the halogen atom include a fluorine atom, a chlorine atom, and a bromine atom.
[0032] Examples of the alkyl group having 1 to 18 carbon atoms include a methyl group, an ethyl group, a propyl group, a butyl group, a pentyl group, a hexyl group, a heptyl group, an octyl group, a nonyl group, a decyl group, a dodecyl group, a tetradecyl group, etc. An alkyl group having 1 to 6 carbon atoms is preferred.
[0033] Examples of the alkoxy group having 1 to 18 carbon atoms include a methoxy group, an ethoxy group, a propoxy group, a butoxy group, a pentoxy group, a hexoxy group, an octoxy group, etc. An alkoxy group having 1 to 6 carbon atoms is preferred.
[0034] Examples of the cycloalkyl group having 6 to 20 carbon atoms include a cyclohexyl group, a cyclooctyl group, etc. A cycloalkyl group having 6 to 12 carbon atoms is preferred.
[0035] Preferred examples of the cycloalkoxy group having 6 to 20 carbon atoms include a cyclohexyloxy group, a cyclooctyloxy group, etc. A cycloalkoxy group having 6 to 12 carbon atoms is preferred.
[0036] Examples of the alkenyl group having 2 to 10 carbon atoms include a methenyl group, an ethenyl group, a propenyl group, a butenyl group, a pentenyl group, etc. An alkenyl group having 2 to 6 carbon atoms is preferred.
[0037] Examples of the aryl group having 6 to 14 carbon atoms include a phenyl group and a naphthyl group.
[0038] Examples of the aryloxy group having 6 to 14 carbon atoms include a phenyloxy group and a naphthyloxy group.
[0039] Examples of the aralkyl group having 7 to 20 carbon atoms include a benzyl group and a phenylethyl group.
[0040] Examples of the aralkyloxy group having 7 to 20 carbon atoms include a benzyloxy group and a phenylethyloxy group.
[0041] Among them, R 1 and R 2 is preferably a hydrogen atom, an alkyl group having 1 to 6 carbon atoms, or an aryl group having 6 to 14 carbon atoms, and particularly preferably a hydrogen atom.
[0042] The content of the repeating unit (a) is 5 to 95 mol %, preferably 10 to 90 mol %, more preferably 10 to 80 mol %, and further preferably 10 to 70 mol %, based on the total repeating units of the copolymerized polycarbonate resin (component A). If it is within the above range, it is preferable because the resin composition with the polycarbonate resin (component B) does not become cloudy due to phase separation during extrusion or molding.
[0043] In the formula (2), R 3 and R 4 each independently represents at least one group selected from the group consisting of a hydrogen atom, a halogen atom, an alkyl group having 1 to 18 carbon atoms, an alkoxy group having 1 to 18 carbon atoms, a cycloalkyl group having 6 to 20 carbon atoms, a cycloalkoxy group having 6 to 20 carbon atoms, an alkenyl group having 2 to 10 carbon atoms, an aryl group having 6 to 14 carbon atoms, an aryloxy group having 6 to 14 carbon atoms, an aralkyl group having 7 to 20 carbon atoms, an aralkyloxy group having 7 to 20 carbon atoms, a nitro group, an aldehyde group, a cyano group, and a carboxyl group, and when there are a plurality of each of these groups, they may be the same or different.
[0044] Here, examples of the alkyl group having 1 to 18 carbon atoms, the alkoxy group having 1 to 18 carbon atoms, the cycloalkyl group having 6 to 20 carbon atoms, the cycloalkoxy group having 6 to 20 carbon atoms, the alkenyl group having 2 to 10 carbon atoms, the aryl group having 6 to 14 carbon atoms, the aryloxy group having 6 to 14 carbon atoms, the aralkyl group having 7 to 20 carbon atoms, and the aralkyloxy group having 7 to 20 carbon atoms include the same groups as described above.
[0045] In the formula (2), W is a single bond or at least one group selected from the group consisting of groups represented by the formula (3).
[0046] In the formula (3), R 5 ,R 6 ,R 7 ,R 8 ,R 9 ,R 10 ,R 11and R 12 each independently represents at least one group selected from the group consisting of a hydrogen atom, an alkyl group having 1 to 18 carbon atoms, an aryl group having 6 to 14 carbon atoms, and an aralkyl group having 7 to 20 carbon atoms, and when there are a plurality of groups, they may be the same or different.
[0047] Examples of the alkyl group having 1 to 18 carbon atoms, the aryl group having 6 to 14 carbon atoms, and the aralkyl group having 7 to 20 carbon atoms include the same groups as those mentioned above.
[0048] In the formula (3), R 13 and R 14 each independently represents at least one group selected from the group consisting of a hydrogen atom, a halogen atom, an alkyl group having 1 to 18 carbon atoms, an alkoxy group having 1 to 18 carbon atoms, a cycloalkyl group having 6 to 20 carbon atoms, a cycloalkoxy group having 6 to 20 carbon atoms, an alkenyl group having 2 to 10 carbon atoms, an aryl group having 6 to 14 carbon atoms, an aryloxy group having 6 to 14 carbon atoms, an aralkyl group having 7 to 20 carbon atoms, an aralkyloxy group having 7 to 20 carbon atoms, a nitro group, an aldehyde group, a cyano group, and a carboxyl group.
[0049] Examples of the alkyl group having 1 to 18 carbon atoms, the alkoxy group having 1 to 18 carbon atoms, the cycloalkyl group having 6 to 20 carbon atoms, the cycloalkoxy group having 6 to 20 carbon atoms, the alkenyl group having 2 to 10 carbon atoms, the aryl group having 6 to 14 carbon atoms, the aryloxy group having 6 to 14 carbon atoms, the aralkyl group having 7 to 20 carbon atoms, and the aralkyloxy group having 7 to 20 carbon atoms include the same groups as described above.
[0050] In the formula (3), R 15 ,R 16 ,R 17 and R 18each independently represents at least one group selected from the group consisting of an alkyl group having 1 to 18 carbon atoms, a cycloalkyl group having 6 to 20 carbon atoms, an alkenyl group having 2 to 10 carbon atoms, an aryl group having 6 to 14 carbon atoms, and an aralkyl group having 7 to 20 carbon atoms, and when there are a plurality of groups, they may be the same or different.
[0051] Examples of the alkyl group having 1 to 18 carbon atoms, the cycloalkyl group having 6 to 20 carbon atoms, the alkenyl group having 2 to 10 carbon atoms, the aryl group having 6 to 14 carbon atoms, and the aralkyl group having 7 to 20 carbon atoms include the same groups as those described above.
[0052] In the formula (3), c is an integer of 1 to 10, preferably an integer of 1 to 4, and more preferably 1. d is an integer of 4 to 7, and preferably 5. h and i are integers of 1 to 3, and preferably 1. g is an integer of 1 to 100, preferably an integer of 10 to 90, and more preferably an integer of 20 to 80.
[0053] It is particularly preferred that the repeating unit (b) represented by the formula (2) contains a repeating unit derived from at least one compound selected from the group consisting of 2,2-bis(4-hydroxy-3-methylphenyl)propane (hereinafter sometimes abbreviated as BPC) and 1,1-bis(4-hydroxy-3-methylphenyl)cyclohexane (hereinafter sometimes abbreviated as OCZ).
[0054] The content of the repeating unit (b) is 5 to 95 mol %, preferably 10 to 90 mol %, more preferably 20 to 90 mol %, and further preferably 30 to 90 mol %, based on the total repeating units of the copolymerized polycarbonate resin (component A). If it is within the above range, it is preferable because the resin composition with the polycarbonate resin (component B) does not become cloudy due to phase separation during extrusion or molding.
[0055] The copolymeric polycarbonate resin (A component) in the present invention may contain, in addition to the repeating units (a) and (b), repeating units derived from other dihydroxy compounds or other diol compounds, as described below, to the extent that the properties of the polycarbonate resin composition are not impaired. The repeating units (c) other than the repeating units (a) and (b) are preferably 30 mol % or less, more preferably 20 mol % or less, even more preferably 10 mol % or less, and particularly preferably 5 mol % or less, based on the total repeating units.
[0056] <Raw material for copolymer polycarbonate resin (Component A)> The repeating unit (a) represented by the formula (1) is derived from a diol compound, specifically, 9,9-bis(6-hydroxy-2-naphthyl)fluorene or 9,9-bis(6-hydroxy-1-naphthyl)fluorene is preferable, and 9,9-bis(6-hydroxy-2-naphthyl)fluorene is more preferable. These diol compounds may be used alone or in combination of two or more.
[0057] The repeating unit (b) represented by the formula (2) is derived from a diol compound, and examples of such a repeating unit include 2,2-bis(4-hydroxyphenyl)propane; 2,2-bis(4-hydroxy-3-methylphenyl)propane; 2,2-bis(4-hydroxy-3-ethylphenyl)propane; 2,2-bis(4-hydroxy-3-propylphenyl)propane; 2,2-bis(4-hydroxy-3-butylphenyl)propane; bis(4-hydroxyphenyl)methane; 1,1-bis(4-hydroxyphenyl)ethane; 2,2-bis (4-hydroxyphenyl)butane;2,2-bis(4-hydroxyphenyl)octane;2,2-bis(4-hydroxyphenyl)phenylmethane;2,2-bis(4-hydroxy-3-methylphenyl)phenylmethane;2,2-bis(4-hydroxy-1-methylphenyl)propane;Bis(4-hydroxyphenyl)naphthylmethane;1,1-bis(4-hydroxy-t-butylphenyl)propane;2,2-bis(4-hydroxy-3-bromophenyl)propane;2,2-bis(4-hydroxy-3,5-tetramethylphenyl)propane Bis(hydroxyaryl)alkanes such as 2,2-bis(4-hydroxy-3-chlorophenyl)propane; 2,2-bis(4-hydroxy-3,5-tetrachlorophenyl)propane; 2,2-bis(4-hydroxy-3,5-tetrabromophenyl)propane, 4,4'-dihydroxyphenyl ether; 4,4'-dihydroxy-3,3'-dimethylphenyl ether and other dihydroxyaryl ethers, 4,4'-dihydroxydiphenyl sulfide; 4,4'-dihydroxy-3,3'- Dihydroxydiaryl sulfides such as dimethyldiphenyl sulfide, 4,4'-dihydroxydiphenyl sulfoxide; dihydroxydiaryl sulfoxides such as 4,4'-dihydroxy-3,3'-dimethyldiphenyl sulfoxide, 4,4'-dihydroxydiphenyl sulfone; dihydroxydiaryl sulfones such as 4,4'-dihydroxy-3,3'-dimethyldiphenyl sulfone, dihydroxydiphenyls such as 4,4'-dihydroxydiphenyl, 9,9-bis(4-hydroxyphenyl)fluorene;Dihydroxydiarylfluorenes such as 9,9-bis(4-hydroxy-3-methylphenyl)fluorene, 1,1-bis(4-hydroxyphenyl)cyclopentane, 1,1-bis(4-hydroxyphenyl)cyclohexane, 1,1-bis(4-hydroxy-3-methylphenyl)cyclopentane, 1,1-bis(4-hydroxy-3-methylphenyl)cyclohexane, 1,1-bis(4-hydroxyphenyl)-3,3,5-trimethylcyclohexane, bis(4-hydroxyphenyl)diphenylmethane , 4,4'-dihydroxybenzophenone, 4,4'-dihydroxy-3,3'-dimethylbenzophenone, 4,4'-biphenol, 3,3',5,5'-tetramethyl-4,4'-biphenyldiol, 3,3'-dimethyl-4,4'-biphenyldiol, α,α'-bis(4-hydroxyphenyl)-1,3-diisopropylbenzene, α,α'-bis(4-hydroxyphenyl)-1,4-diisopropylbenzene, 2-phenyl-3,3-bis(p-hydroxyphenyl)phthalimidine, etc.;
[0058] Among these, 2,2-bis(4-hydroxy-3-methylphenyl)propane (BPC) and 1,1-bis(4-hydroxy-3-methylphenyl)cyclohexane (OCZ) are preferred. These diols may be used alone or in combination of two or more.
[0059] In the copolymer polycarbonate resin (component A) of the present invention, other dihydroxy compounds and diol compounds may be copolymerized in addition to the repeating units (a) and (b) to the extent that the properties of the polycarbonate resin composition are not impaired.
[0060] Other dihydroxy compounds include hydroquinone, resorcinol, orcinol, 2,2-bis(4-hydroxyphenyl)norbornene, 1,3-bis(4-hydroxyphenyl)adamantane; 2,2-bis(4-hydroxyphenyl)adamantane; 1,3-bis(4-hydroxyphenyl)-5,7-dimethyladamantane, 10,10-bis(4-hydroxyphenyl)-9-anthrone, 1,5-bis(4-hydroxyphenylthio)-2,3-dioxapentaenebisphenoxyethanolfluorene, and the like.
[0061] Other diol compounds include isosorbide:1,4:3,6-dianhydro-D-sorbitol, tricyclodecane dimethanol (TCDDM), 4,8-bis(hydroxymethyl)tricyclodecane, tetramethylcyclobutanediol (TMCBD), 2,2,4,4-tetramethylcyclobutane-1,3-diol, mixed isomers, cis / trans-1,4-cyclohexanedimethanol (CHDM), cis / trans-1,4-bis(hydroxymethyl)cyclohexane, and cyclohex-1,4-ylenedimethanol. Examples of such cyclohexanedimethanol include 1,1'-bi(cyclohexyl)-4,4'-diol, spiroglycol, dicyclohexyl-4,4'-diol, 4,4'-dihydroxybicyclohexyl, and poly(ethylene glycol).
[0062] <Production method of copolymer polycarbonate resin (component A)> The copolymeric polycarbonate resin in the present invention is obtained by reacting the diol compound (component A) with a carbonate precursor. Examples of the reaction method include an interfacial polycondensation method, a melt transesterification method, a solid-phase transesterification method of a carbonate prepolymer, and a ring-opening polymerization method of a cyclic carbonate compound. In the case of interfacial polycondensation, a terminal terminator of a monohydric phenol is usually used.
[0063] The copolymerized polycarbonate resin (component A) contains polyester carbonate copolymerized with aromatic or aliphatic (including alicyclic) bifunctional carboxylic acids. The aliphatic bifunctional carboxylic acids are preferably α,ω-dicarboxylic acids. Examples of the aliphatic bifunctional carboxylic acids include linear saturated aliphatic dicarboxylic acids such as sebacic acid (decanedioic acid), dodecanedioic acid, tetradecanedioic acid, octadecanedioic acid, and icosane diacid, and alicyclic dicarboxylic acids such as cyclohexane dicarboxylic acid. These carboxylic acids may be copolymerized to the extent that the purpose is not hindered. In addition, the copolymerized polycarbonate resin (component A) may also be copolymerized with a structural unit containing a polyorganosiloxane unit as necessary.
[0064] The copolymeric polycarbonate resin (Component A) can also be made into a branched polycarbonate by copolymerizing a structural unit containing a trifunctional or higher polyfunctional aromatic compound, if necessary.
[0065] Suitable examples of trifunctional or higher polyfunctional aromatic compounds used in branched polycarbonates include 4,6-dimethyl-2,4,6-tris(4-hydroxyphenyl)heptene-2, 2,4,6-trimethyl-2,4,6-tris(4-hydroxyphenyl)heptane, 1,3,5-tris(4-hydroxyphenyl)benzene, 1,1,1-tris(4-hydroxyphenyl)ethane, 1,1,1-tris(3,5-dimethyl-4-hydroxyphenyl)ethane, 2,6-bis(2-hydroxy-5-methylbenzyl)-4-methylphenol, and trisphenols such as 4-{4-[1,1-bis(4-hydroxyphenyl)ethyl]benzene}-α,α-dimethylbenzylphenol. Among these, 1,1,1-tris(4-hydroxyphenyl)ethane is preferred. The constituent units derived from such polyfunctional aromatic compounds preferably account for 0.03 to 1.5 mol %, more preferably 0.1 to 1.2 mol %, and particularly preferably 0.2 to 1.0 mol %, of a total of 100 mol %, including the constituent units from other diol components.
[0066] The branched structural unit may be derived not only from a polyfunctional aromatic compound, but also from a side reaction occurring during a polymerization reaction by a melt transesterification method without using a polyfunctional aromatic compound. 1 It can be calculated by H-NMR measurement.
[0067] In a reaction using, for example, phosgene as a carbonate precursor, the reaction is usually carried out in the presence of an acid binder and a solvent. As the acid binder, for example, an alkali metal hydroxide such as sodium hydroxide or potassium hydroxide, or an amine compound such as pyridine, is used. As the solvent, for example, a halogenated hydrocarbon such as methylene chloride or chlorobenzene is used. In addition, a catalyst such as a tertiary amine or a quaternary ammonium salt can be used to promote the reaction. In this case, the reaction temperature is usually 0 to 40°C, and the reaction time is several minutes to 5 hours.
[0068] The transesterification reaction using, for example, a carbonic acid diester as a carbonate precursor is carried out by a method of heating and stirring a predetermined ratio of aromatic diol components with a carbonic acid diester under an inert gas atmosphere, and distilling off the resulting alcohol or phenol. The reaction temperature varies depending on the boiling point of the resulting alcohol or phenol, but is usually in the range of 120 to 300°C. The reaction is completed by reducing the pressure from the beginning of the reaction and distilling off the resulting alcohol or phenol. In order to promote the reaction, a catalyst usually used in transesterification reactions can also be used. Examples of the carbonic acid diester used in the transesterification reaction include diphenyl carbonate, dinaphthyl carbonate, bis(diphenyl)carbonate, dimethyl carbonate, diethyl carbonate, and dibutyl carbonate. Among these, diphenyl carbonate is particularly preferred.
[0069] Monofunctional phenols that are commonly used as end terminators can be used. In particular, in the case of a reaction using phosgene as a carbonate precursor, monofunctional phenols are generally used as end terminators to adjust molecular weight, and the obtained polycarbonate resin has excellent thermal stability compared to those that are not, since the ends are blocked by groups based on monofunctional phenols. Specific examples of the monofunctional phenols include phenol, m-methylphenol, p-methylphenol, m-propylphenol, p-propylphenol, 1-phenylphenol, 2-phenylphenol, p-tert-butylphenol, p-cumylphenol, isooctylphenol, and p-long chain alkylphenol.
[0070] (viscosity average molecular weight) The viscosity average molecular weight of the copolymerized polycarbonate resin (component A) in the present invention is preferably in the range of 6,000 to 35,000, more preferably in the range of 7,000 to 30,000, even more preferably in the range of 8,000 to 28,000, particularly preferably in the range of 9,000 to 25,000, and most preferably in the range of 10,000 to 22,000. If it is within the above range, in a resin composition with the polycarbonate resin (component B), phase separation does not occur during extrusion or molding, and the resin composition does not become cloudy, and is preferable in terms of excellent heat resistance, scratch resistance, and impact resistance.
[0071] The viscosity average molecular weight of the polycarbonate resin in the present invention is calculated by first calculating the specific viscosity (η SP ) was measured at 20°C using an Ostwald viscometer from a solution of 0.7 g of resin in 100 ml of methylene chloride. Specific viscosity (η SP )=(tt 0 ) / t 0 [t 0 is the time it takes for methylene chloride to fall, and t is the time it takes for the sample solution to fall] The specific viscosity (η SP ) and the viscosity average molecular weight Mv was calculated using the following formula: η SP / c=[η]+0.45×[η] 2 c (where [η] is the intrinsic viscosity) [η]=1.23×10 -4 Mv 0.83 c=0.7
[0072] (Glass transition temperature: Tg) The glass transition temperature (Tg) of the copolymerized polycarbonate resin (component A) in the present invention is preferably in the range of 100 to 300°C, more preferably in the range of 120 to 280°C, and even more preferably in the range of 130 to 270°C. When Tg is within the above range, in a resin composition with the polycarbonate resin (component B), phase separation does not occur during extrusion or molding, and the resin composition does not become cloudy, and the heat resistance and moldability are good, which is preferable. The glass transition temperature (Tg) is measured using a 2910-type DSC manufactured by TA Instruments Japan Co., Ltd. at a heating rate of 20°C / min.
[0073] <Aromatic polycarbonate resin (Component B)> The aromatic polycarbonate resin (B component) of the present invention may be either a homopolymer or a copolymer. In addition, the aromatic polycarbonate resin (B) may have a branched structure or a linear structure, or may be a mixture of a branched structure and a linear structure.
[0074] As a method for producing the aromatic polycarbonate resin (B) using a dihydric phenol as a raw material, any known method such as a phosgene method, an ester exchange method, or a pyridine method may be used.
[0075] Representative examples of dihydric phenols include bisphenols, and in particular, 2,2-bis(4-hydroxyphenyl)propane, i.e., bisphenol A, is preferably used. Bisphenol A may be partially or entirely replaced with another dihydric phenol. Other dihydric phenols include hydroquinone, 4,4-dihydroxydiphenyl, bis(4-hydroxyphenyl)alkanes such as bis(4-hydroxyphenyl)methane and 1,1-bis(4-hydroxyphenyl)ethane, bis(4-hydroxyphenyl)cycloalkanes such as 1,1-bis(4-hydroxyphenyl)cyclohexane, bis(4-hydroxyphenyl)sulfide, bis(4-hydroxyphenyl)sulfone, bis(4-hydroxyphenyl)sulfoxide, and bis(4-hydroxyphenyl)ether compounds, alkylated bisphenols such as 2,2-bis(3-methyl-4-hydroxyphenyl)propane and 2,2-bis(3,5-dimethyl-4-hydroxyphenyl)propane, and halogenated bisphenols such as 2,2-bis(3,5-dibromo-4-hydroxyphenyl)propane and 2,2-bis(3,5-dichloro-4-hydroxyphenyl)propane. Among the bisphenols, an aromatic polycarbonate resin obtained by using bisphenol A in an amount of preferably 50 mol % or more, more preferably 70 mol % or more, further preferably 90 mol % or more, and particularly preferably 100 mol % is desirable.
[0076] (viscosity average molecular weight) The viscosity average molecular weight of the aromatic polycarbonate resin (component B) used in the present invention is not particularly limited, but is preferably in the range of 15,000 to 35,000, more preferably 18,000 to 32,000, in view of the balance between heat resistance, impact resistance, and moldability in the resin composition. Here, the specific viscosity (η SP ) was measured at 20°C using an Ostwald viscometer from a solution of 0.7 g of sample dissolved in 100 ml of methylene chloride. Specific viscosity (η SP )=(tt 0 ) / t 0 [t0 is the time it takes for methylene chloride to fall, and t is the time it takes for the sample solution to fall] The specific viscosity (η SP ) and the viscosity average molecular weight Mv was calculated using the following formula: η SP / c=[η]+0.45×[η] 2 c (where [η] is the intrinsic viscosity) [η]=1.23×10 -4 Mv 0.83 c=0.7
[0077] (Glass transition temperature: Tg) The aromatic polycarbonate resin (B) has a glass transition temperature (Tg) of preferably 120 to 180° C., more preferably 140 to 160° C. When the Tg is within the above range, the resulting polycarbonate resin composition has good heat resistance and impact resistance, which is preferable. The glass transition temperature (Tg) is measured using a 2910 model DSC manufactured by TA Instruments Japan, Inc. at a heating rate of 20°C / min.
[0078] <Production method of polycarbonate resin composition and molded article> In producing the resin composition of the present invention, the production method is not particularly limited, and known production methods can be used. Usually, the copolymer polycarbonate resin (A), the aromatic polycarbonate resin (B) and the additives are premixed, then fed into an extruder and melt-kneaded, and the extruded thread is cooled and cut by a pelletizer to produce a pellet-shaped molding material. The extruder may be either a single-screw extruder or a twin-screw extruder, but from the viewpoint of productivity and kneading, a twin-screw extruder is preferred. Representative examples of such twin-screw extruders include KZW15-25MG (manufactured by Technobel Co., Ltd.) and ZSK (manufactured by Werner & Pfleiderer). Specific examples of similar types include TEX (manufactured by Japan Steel Works, Ltd.), TEM (manufactured by Toshiba Machine Co., Ltd.), and KTX (manufactured by Kobe Steel, Ltd.). As the extruder, one having a vent that can degas the moisture in the raw materials and the volatile gas generated from the melt-kneaded resin can be preferably used. A vacuum pump is preferably installed from the vent to efficiently discharge the generated moisture and volatile gases to the outside of the extruder. It is also possible to install a screen in the zone before the extruder die section to remove foreign matter mixed in the extrusion raw material, and to remove the foreign matter from the resin composition. Examples of such a screen include a wire mesh, a screen changer, and a sintered metal plate (such as a disk filter).
[0079] Furthermore, although the additives can be fed independently to the extruder, it is preferable to premix them with the resin raw material as described above. Examples of such premixing means include a Nauta mixer, a V-type blender, a Henschel mixer, a mechanochemical device, and an extrusion mixer. A more suitable method is, for example, to mix a part of the raw material and the additives with a high-speed mixer such as a Henschel mixer to prepare a master agent, and then to mix the master agent with the remaining resin raw material in a low-speed mixer such as a Nauta mixer.
[0080] The resin extruded from the extruder is directly cut and pelletized, or the strands are formed and then cut by a pelletizer to pelletize. When it is necessary to reduce the influence of external dust, it is preferable to purify the atmosphere around the extruder. Furthermore, in the production of such pellets, it is preferable to narrow the shape distribution of the pellets, further reduce miscuts, further reduce fine powder generated during transportation or transport, and reduce bubbles (vacuum bubbles) generated inside the strands and pellets using various methods that have already been proposed. Miscuts can be reduced by means of temperature management of the thread during cutting with a pelletizer, blowing ion wind during cutting, optimizing the rake angle of the pelletizer, and appropriately blending a release agent, as well as a method of filtering a mixture of cut pellets and water to separate the pellets from the water and miscuts. An example of the measurement method is disclosed in, for example, JP-A-2003-200421. These prescriptions can be used to achieve high cycle molding and reduce the rate of defects such as silver.
[0081] The resin composition of the present invention can be used to obtain a desired molded product by injection molding, injection compression molding, injection blow molding, extrusion molding, blow molding, or other methods. Furthermore, the molded product of the present invention can be subjected to various surface treatments. The surface treatment referred to here is a method for forming a new layer on the surface of a resin molded product, such as vapor deposition (physical vapor deposition, chemical vapor deposition, etc.), plating (electroplating, electroless plating, hot-dip plating, etc.), painting, coating, printing, etc., and methods used for ordinary thermoplastic resins can be applied. Specific examples of the surface treatment include various surface treatments such as hard coat, water-repellent / oil-repellent coat, ultraviolet absorbing coat, infrared absorbing coat, and metallizing (vapor deposition, etc.).
[0082] The polycarbonate resin composition of the present invention may contain various additives to impart various properties to the extent that the object of the present invention is not impaired. The additives may include a release agent, a heat stabilizer, an ultraviolet absorber, a bluing agent, an antistatic agent, a flame retardant, a heat shielding agent, a fluorescent dye (including a fluorescent brightener), a pigment, a light diffusing agent, a reinforcing filler, other resins, elastomers, etc.
[0083] The release agent is preferably one that is composed of 90% by weight or more of an ester of alcohol and fatty acid. Specific examples of the ester of alcohol and fatty acid include ester of monohydric alcohol and fatty acid, and partial or complete ester of polyhydric alcohol and fatty acid. Specific examples of the ester of monohydric alcohol and saturated fatty acid include stearyl stearate, palmityl palmitate, butyl stearate, methyl laurate, isopropyl palmitate, etc. Stearyl stearate is preferred. Examples of the partial or full ester of a polyhydric alcohol and a saturated fatty acid include stearic acid monoglyceride, stearic acid diglyceride, stearic acid triglyceride, stearic acid monosorbitate, behenic acid monoglyceride, pentaerythritol monostearate, pentaerythritol tetrastearate, pentaerythritol tetrapelargonate, propylene glycol monostearate, biphenyl biphenate, sorbitan monostearate, 2-ethylhexyl stearate, dipentaerythritol hexastearate, and other full or partial esters of dipentaerythritol. Among these esters, stearic acid monoglyceride, stearic acid triglyceride, pentaerythritol tetrastearate, and a mixture of stearic acid triglyceride and stearyl stearate are preferred, and stearic acid monoglyceride and pentaerythritol tetrastearate are more preferred.
[0084] The amount of the release agent to be added is preferably in the range of 0.05 to 0.5 parts by weight, more preferably in the range of 0.1 to 0.4 parts by weight, and further preferably in the range of 0.12 to 0.3 parts by weight, based on 100 parts by weight of the polycarbonate resin composition.
[0085] Examples of the heat stabilizer include phosphorus-based heat stabilizers, sulfur-based heat stabilizers, and hindered phenol-based heat stabilizers. Examples of the phosphorus-based heat stabilizer include phosphorous acid, phosphoric acid, phosphonous acid, phosphonic acid, and esters thereof. Specifically, bis(2,4-dicumylphenyl)pentaerythritol diphosphite, tris(2,4-di-tert-butylphenyl)phosphite, tris(2,6-di-tert-butylphenyl)phosphite, 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate stearyl, [1,1-biphenyl]-4,4-diylbis[bis(2,4-di-tert-butylphenoxy)phosphine], 3,9-bis(2,6-di-tert-butylphenyl)propionate, ... butyl-4-methylphenoxy)-2,4,8,10-tetraoxa-3,9-diphosphaspiro[5.5]undecane is preferred, and tris(2,4-di-tert-butylphenyl)phosphite, 3-(3,5-di-tert-butyl-4-hydroxyphenyl)stearyl propionate, and 3,9-bis(2,6-di-tert-butyl-4-methylphenoxy)-2,4,8,10-tetraoxa-3,9-diphosphaspiro[5.5]undecane are more preferred.
[0086] The amount of the heat stabilizer to be added is preferably in the range of 0.001 to 0.5 parts by weight, more preferably in the range of 0.005 to 0.4 parts by weight, and further preferably in the range of 0.01 to 0.3 parts by weight, based on 100 parts by weight of the polycarbonate resin composition.
[0087] (weight ratio) The weight ratio of the copolymer polycarbonate resin (component A) to the aromatic polycarbonate resin (component B) can be arbitrarily mixed within the range of 1:99 to 99:1. The range is preferably 5:95 to 95:5, and more preferably 10:90 to 90:10. By keeping the ratio within the above range, a polycarbonate resin composition having excellent heat resistance, scratch resistance, and impact resistance can be obtained.
[0088] (viscosity average molecular weight) The viscosity average molecular weight of the polycarbonate resin composition in the present invention is preferably in the range of 6,000 to 35,000, more preferably in the range of 8,000 to 32,000, still more preferably in the range of 10,000 to 30,000, particularly preferably in the range of 13,000 to 28,000, and most preferably in the range of 15,000 to 25,000. This is preferred because it has excellent heat resistance, scratch resistance, and impact resistance.
[0089] The viscosity average molecular weight of the polycarbonate resin composition in the present invention is calculated by first calculating the specific viscosity (η SP ) was measured at 20°C using an Ostwald viscometer from a solution of 0.7 g of resin in 100 ml of methylene chloride. Specific viscosity (η SP )=(tt 0 ) / t 0 [t 0 is the time it takes for methylene chloride to fall, and t is the time it takes for the sample solution to fall] The specific viscosity (η SP ) and the viscosity average molecular weight Mv was calculated using the following formula: η SP / c=[η]+0.45×[η] 2 c (where [η] is the intrinsic viscosity) [η]=1.23×10 -4 Mv 0.83 c=0.7
[0090] (Glass transition temperature: Tg) The glass transition temperature (Tg) of the polycarbonate resin composition in the present invention is preferably single, and the temperature range is preferably 100 to 300°C, more preferably 120 to 250°C, even more preferably 130 to 220°C, and particularly preferably 140 to 200°C. When Tg is within the above range, the resin composition with the polycarbonate resin (B component) does not phase separate during extrusion or molding, and the resin composition does not become cloudy, and is preferable in terms of heat resistance and moldability. The glass transition temperature (Tg) is measured using a 2910-type DSC manufactured by TA Instruments Japan Co., Ltd. at a heating rate of 20°C / min. In the present invention, when the glass transition temperature (Tg) is single, only one inflection point indicating the glass transition temperature appears when the glass transition temperature is measured using DSC.
[0091] Generally, when a polymer blend composition has a single glass transition temperature, it means that the mixed resins are in a compatible state on the nanometer order (molecular level), and the system can be considered to be compatible.
[0092] (Transparency: total light transmittance) The polycarbonate resin composition of the present invention preferably has a total light transmittance of 85% or more for a molded piece having a thickness of 2 mm. If the total light transmittance is within the above range, the range of use as an optical member is not limited, which is preferable.
[0093] (Indentation hardness) The polycarbonate resin composition of the present invention has an indentation hardness of 150 to 400 (N / mm 2 ), and 170 to 350 (N / mm 2 ), and more preferably 200 to 300 (N / mm 2 ), and particularly preferably 215 to 290 (N / mm 2 ), and most preferably 225 to 280 (N / mm 2 When the indentation hardness is within the above range, the molded product has excellent scratch resistance.
[0094] In addition, pencil hardness, which is a commonly used index for the scratch resistance of materials, is a discrete index with a range, so it is difficult to compare the hardness of materials with the same pencil hardness of "2H," for example. Therefore, by using indentation hardness, which allows for quantitative evaluation, as an index, it is possible to evaluate the degree of hardness even for materials with the same pencil hardness.
[0095] The indentation hardness is measured based on ISO / TS 19278 by using a dynamic ultra-microhardness tester (Shimadzu Corporation, model DUH-210S) to measure the relationship between the load and the indentation depth on the surface of the resin plate in real time.
[0096] (Pencil hardness) The pencil hardness of the polycarbonate resin composition in the present invention is preferably H or more, more preferably 2H or more, and even more preferably 3H or more. The pencil hardness is a hardness at which no scratch marks remain when the polycarbonate resin is scratched with a pencil having a specific pencil hardness, and it is preferable to use the pencil hardness used in the surface hardness test of the coating film that can be measured according to JIS K-5600 as an index. The pencil hardness becomes softer in the order of 9H, 8H, 7H, 6H, 5H, 4H, 3H, 2H, H, F, HB, B, 2B, 3B, 4B, 5B, and 6B, with the hardest being 9H and the softest being 6B. When the pencil hardness is above the above level, the molded product has excellent scratch resistance.
[0097] (Charpy notched impact value) The polycarbonate resin composition of the present invention has a notched Charpy impact strength measured in accordance with ISO 179 of 1.5 kJ / m 2 It is preferable that the concentration is 2.0 kJ / m or more. 2 More preferably, it is 3.0 kJ / m or more. 2 More preferably, the notched Charpy impact strength is 100 kJ / m or more. 2 The following functions are sufficient.
[0098] (Weight drop resistance test: DuPont impact test) It is preferable that the polycarbonate resin composition of the present invention is not destroyed when a 1 kg weight is dropped from a height of 1 m using a DuPont impact deformation tester with a striking die (radius 6.35 mm) and a receiving die (inner diameter 15.2 mm, outer diameter 25.0 mm) and a parallel plate 50 mm in length and width and 2 mm in thickness placed between the receiving die and the striking die. EXAMPLES
[0099] The present invention will be described in more detail below with reference to examples, but the present invention is not limited thereto. The evaluation was performed according to the following methods.
[0100] (1) Composition ratio Each repeating unit was measured by proton NMR using JNM-AL400 manufactured by JEOL Ltd., and the composition ratio (mol %) of the polycarbonate resin was calculated.
[0101] (2) Viscosity average molecular weight The specific viscosity (η SP ) was measured at 20°C using an Ostwald viscometer from a solution of 0.7 g of sample dissolved in 100 ml of methylene chloride. Specific viscosity (η SP )=(tt 0 ) / t 0 [t 0 is the time it takes for methylene chloride to fall, and t is the time it takes for the sample solution to fall] The specific viscosity (η SP ) and the viscosity average molecular weight Mv was calculated using the following formula: η SP / c=[η]+0.45×[η] 2 c (where [η] is the intrinsic viscosity) [η]=1.23×10 -4 Mv 0.83 c=0.7
[0102] (3) Total light transmittance The resin pellets were dried at 120°C for 12 hours, and then molded into a three-level resin plate having a length of 90 mm and thicknesses of 3 mm (length 20 mm), 2 mm (length 45 mm), and 1 mm (length 25 mm) from the gate side using an injection molding machine (J-75E3 manufactured by Japan Steel Works) at a cylinder temperature of 280-340°C and a mold temperature of 90-120°C. The 2 mm thick part of the molded three-level resin plate was measured using a haze meter 300A manufactured by Nippon Denshoku Industries Co., Ltd., and evaluated according to the following criteria. "Good": Total light transmittance is 85% or more "X": Total light transmittance is less than 85%
[0103] (4) Glass transition temperature (Tg) The measurements were performed using a TA Instruments Japan Co., Ltd. Model 2910 DSC by heating approximately 10 mg of the sample at a heating rate of 20°C / min.
[0104] (5) Deflection temperature under load The deflection temperature under load of 0.45 MPa was measured in accordance with ISO75.
[0105] (6) Indentation hardness Using a 2 mm thick section of the molded three-stage resin plate, a dynamic ultra-microhardness tester (Shimadzu Corporation, model DUH-210S) was used to measure the relationship between the load and the indentation depth on the plate surface in real time in accordance with ISO / TS 19278, and the indentation hardness (N / mm 2 ) was measured. (Measurement conditions) Measurement indenter: Berkovich indenter (made of diamond) Test force: 500mN Minimum test force: 4.9mN Loading / unloading time: 30sec Load holding time: 40sec Unloading holding time: 0sec Number of tests: 5 (Method of calculating indentation hardness) Indentation hardness (Hit) is a measure of the resistance to semi-permanent deformation or damage. Indentation hardness is calculated using the following formula: Hit=F max / Ap F max : Maximum test force A p : Projected area where the indenter and the test piece are in contact A p =23.96×h c 2 (In the case of a triangular pyramid indenter (115°)) h c =h max -ε(h max -h r ) ε=3 / 4 (in the case of a triangular pyramid) h r : F of the test force-depth curve max The intercept where the tangent to the unloading curve at
[0106] (7) Pencil hardness Using a 2 mm thick section of the molded three-tiered resin plate, a line was drawn with a pencil at a 45 degree angle to the surface of the resin plate while applying a load of 750 g in a temperature-controlled room at an ambient temperature of 23°C, in accordance with JIS K5600, and the surface condition was visually evaluated. Load capacity: 750g Measurement speed: 50mm / min Measurement distance: 7mm Pencil: Mitsubishi Hi-uni
[0107] (8) Charpy notched impact value The pellets of the polycarbonate resin composition were dried at 90 to 120° C. for 12 hours, and then molded into bending test pieces at a cylinder temperature of 230 to 350° C. and a mold temperature of 80 to 120° C. using a JSWJ-75EIII manufactured by Japan Steel Works, Ltd. The notched Charpy impact test was performed according to ISO179.
[0108] (9) Drop weight resistance test: DuPont impact test A DuPont impact deformation test was carried out using the 2mm thick part of the molded three-stage resin plate. Using a DuPont impact deformation test, a striking die (radius 6.35mm) and a receiving die (inner diameter 15.2mm, outer diameter 25.0mm) were used, and a 2mm thick resin plate was placed between the receiving die and striking die, and a 1kg weight was dropped from a height of 1m. The state of destruction was visually observed and evaluated according to the following criteria. "Good": The molded product was not destroyed and no cracks or breaks occurred. "X": The molded product was destroyed, or cracks or fractures occurred in the molded product.
[0109] [Copolymer polycarbonate resin (Component A)] Resin-1: copolymer composition BNF / BPC=38 / 62 mol%, viscosity average molecular weight=17,200, glass transition temperature=180°C. Resin-2: copolymer composition BNF / OCZ=38 / 62 mol%, viscosity average molecular weight=17,300, glass transition temperature=192°C. Resin-3: copolymer composition BNF / BPC=50 / 50 mol%, viscosity average molecular weight=17,200, glass transition temperature=205°C. Resin-4: copolymer composition BNF / BPC=20 / 80 mol%, viscosity average molecular weight=17,200, glass transition temperature=155°C. Resin-5: copolymer composition BNF / BPC=10 / 90 mol%, viscosity average molecular weight=17,100, glass transition temperature=137°C.
[0110] [Aromatic polycarbonate resin (Component B)] Resin-7: Panlite L-1250 manufactured by Teijin Ltd. (composition: bisphenol A 100 mol%, viscosity average molecular weight = 24,000) Resin-8: Panlite K-1300 manufactured by Teijin Ltd. (composition: bisphenol A 100 mol%, viscosity average molecular weight = 30,000)
[0111] [Other resins] Resin-9: Mitsubishi Chemical Acrypet VH-001
[0112] [Example 1] <Production of copolymer polycarbonate resin (component A)> In a reactor equipped with a thermometer, a stirrer, and a reflux condenser, 19636 parts by weight of ion-exchanged water and 6012 parts by weight of 25% aqueous sodium hydroxide solution were placed, and 1911 parts by weight of 9,9-bis(6-hydroxy-2-naphthyl)fluorene (BNF; manufactured by Osaka Gas Chemical Co., Ltd.), 2017 parts by weight of 2,2-bis(4-hydroxy-3-methylphenyl)propane (BPC; manufactured by Honshu Chemical Co., Ltd.) and 7.86 parts by weight of hydrosulfite were dissolved as diol compounds, and then 15455 parts by weight of methylene chloride was added, and 1500 parts by weight of phosgene was blown in over 80 minutes at 16 to 24 ° C. with stirring. Then, a solution of 970 parts by weight of 25% aqueous sodium hydroxide solution and 61.82 parts by weight of p-tert-butylphenol dissolved in 618 parts by weight of methylene chloride was added and stirred to form an emulsion. Under such stirring, 3.06 parts by weight of triethylamine was added when the reaction solution was at 28°C, and the reaction was terminated by continuing stirring at a temperature of 26 to 31°C for 1 hour. After the reaction was terminated, the organic phase was separated, diluted with methylene chloride, and repeatedly washed with ion-exchanged water, and when the washing solution became neutral, hydrochloric acid was added. Thereafter, the mixture was repeatedly washed with ion-exchanged water until the conductivity of the aqueous phase was almost the same as that of the ion-exchanged water, and a methylene chloride solution of polycarbonate was obtained. Next, the obtained methylene chloride solution was dropped into warm water kept at 50 to 80°C, and the solvent was evaporated and removed to obtain a powder-like solid. The obtained solid was dried at 120°C for 24 hours to obtain a white powder-like copolymer polycarbonate resin (resin-1).
[0113] <Production of polycarbonate resin composition> Resin-1 (component A) and resin-7 (component B) were mixed so that the blend weight ratio was 90:10, and then the mixture was melt-kneaded at 320°C in both the cylinder and die of a vented twin-screw extruder [KZW15-25MG manufactured by Technobel Co., Ltd.] to obtain blend pellets of copolymer polycarbonate resin and aromatic polycarbonate resin. A part of the obtained pellets was dried at 120°C for 12 hours or more, and then molded into test pieces for various evaluations using an injection molding machine (J-75E3 manufactured by Japan Steel Works) under conditions of a cylinder temperature of 320°C and a mold temperature of 100°C. The evaluation results are shown in Table 1. The glass transition temperature of the obtained blend pellets was single.
[0114] [Example 2] <Production of polycarbonate resin composition> Except for the blend weight ratio of resin-1 / resin-7 being 80:20, the same operations and evaluations were carried out as in Example 1. The evaluation results are shown in Table 1. The glass transition temperature of the obtained blend pellets was uniform.
[0115] [Example 3] <Production of polycarbonate resin composition> Except for using Resin-8 instead of Resin-7 as the aromatic polycarbonate resin (B component) and changing the blend weight ratio to Resin-1 / Resin-8=70:30, the same operations and evaluations were carried out as in Example 1. The evaluation results are shown in Table 1. The glass transition temperature of the obtained blend pellets was uniform.
[0116] [Example 4] <Production of polycarbonate resin composition> Except for the blend weight ratio of resin-1 / resin-7 being 70:30, the same operations and evaluations were carried out as in Example 1. The evaluation results are shown in Table 1. The glass transition temperature of the obtained blend pellets was uniform.
[0117] [Example 5] <Production of polycarbonate resin composition> Except for the blend weight ratio of resin-1 / resin-7 being 60:40, the same operations and evaluations were carried out as in Example 1. The evaluation results are shown in Table 1. The glass transition temperature of the obtained blend pellets was uniform.
[0118] [Example 6] <Production of polycarbonate resin composition> Except for the blend weight ratio of resin-1 / resin-7 being 50:50, the same operations and evaluations were carried out as in Example 1. The evaluation results are shown in Table 1. The glass transition temperature of the obtained blend pellets was uniform.
[0119] [Example 7] <Production of polycarbonate resin composition> Except for the blend weight ratio of resin-1 / resin-7 being 10:90, the same operations and evaluations were carried out as in Example 1. The evaluation results are shown in Table 1. The glass transition temperature of the obtained blend pellets was uniform.
[0120] [Example 8] <Production of copolymer polycarbonate resin (component A)> The same procedure as in Example 1 was carried out except that the diol compounds used were 1911 parts by weight of 9,9-bis(6-hydroxy-2-naphthyl)fluorene (BNF; manufactured by Osaka Gas Chemical Co., Ltd.), 2335 parts by weight of 1,1-bis(4-hydroxy-3-methylphenyl)cyclohexane (OCZ; manufactured by Honshu Chemical Co., Ltd.), and 8.49 parts by weight of hydrosulfite, to obtain a white powdery copolymer polycarbonate resin (resin-2).
[0121] <Production of polycarbonate resin composition> Except for the blend weight ratio of resin-2 / resin-7 being 50:50, the same operations and evaluations were carried out as in Example 1. The evaluation results are shown in Table 1. The glass transition temperature of the obtained blend pellets was uniform.
[0122] [Example 9] <Production of copolymer polycarbonate resin (component A)> The same procedure as in Example 1 was carried out except that 2730 parts by weight of 9,9-bis(6-hydroxy-2-naphthyl)fluorene (BNF; manufactured by Osaka Gas Chemical Co., Ltd.), 1551 parts by weight of 2,2-bis(4-hydroxy-3-methylphenyl)propane (BPC; manufactured by Honshu Chemical Co., Ltd.), and 8.56 parts by weight of hydrosulfite were used as the diol compound, and a white powdery copolymeric polycarbonate resin (resin-3) was obtained.
[0123] <Production of polycarbonate resin composition> Except for the blend weight ratio of resin-3 / resin-7 being 50:50, the same operations and evaluations were carried out as in Example 1. The evaluation results are shown in Table 1. The glass transition temperature of the obtained blend pellets was uniform.
[0124] [Example 10] <Production of copolymer polycarbonate resin (component A)> The same procedure as in Example 1 was carried out except that 1092 parts by weight of 9,9-bis(6-hydroxy-2-naphthyl)fluorene (BNF; manufactured by Osaka Gas Chemical Co., Ltd.), 2482 parts by weight of 2,2-bis(4-hydroxy-3-methylphenyl)propane (BPC; manufactured by Honshu Chemical Co., Ltd.) and 7.15 parts by weight of hydrosulfite were used as the diol compound, and a white powdery copolymeric polycarbonate resin (resin-4) was obtained.
[0125] <Production of polycarbonate resin composition> Except for the blend weight ratio of resin-4 / resin-7 being 50:50, the same operations and evaluations were carried out as in Example 1. The evaluation results are shown in Table 1. The glass transition temperature of the obtained blend pellets was uniform.
[0126] [Example 11] <Production of copolymer polycarbonate resin (component A)> The same procedure as in Example 1 was carried out except that 546 parts by weight of 9,9-bis(6-hydroxy-2-naphthyl)fluorene (BNF; manufactured by Osaka Gas Chemical Co., Ltd.), 2792 parts by weight of 2,2-bis(4-hydroxy-3-methylphenyl)propane (BPC; manufactured by Honshu Chemical Co., Ltd.), and 6.68 parts by weight of hydrosulfite were used as the diol compound, and a white powdery copolymeric polycarbonate resin (resin-5) was obtained.
[0127] <Production of polycarbonate resin composition> Except for the blend weight ratio of resin-5 / resin-7 being 50:50, the same operations and evaluations were carried out as in Example 1. The evaluation results are shown in Table 1. The glass transition temperature of the obtained blend pellets was uniform.
[0128] [Comparative Example 1] After drying the resin-7 pellets at 120°C for 12 hours or more, test pieces for various evaluations were molded using an injection molding machine (Japan Steel Works, J-75E3) at a cylinder temperature of 350°C and a mold temperature of 120°C. The evaluation results are shown in Table 1.
[0129] [Comparative Example 2] After drying the resin-9 pellets at 90° C. for 12 hours or more, test pieces for various evaluations were molded using an injection molding machine (Japan Steel Works, J-75E3) at a cylinder temperature of 230° C. and a mold temperature of 80° C. The evaluation results are shown in Table 1.
[0130] [Table 1] [Industrial Applicability]
[0131] Since the polycarbonate resin composition of the present invention has excellent heat resistance, transparency, scratch resistance and impact resistance, it does not require a coating treatment and can be used for automobile interior parts such as lamp lenses for interior lighting, display meter covers, meter dial plates, various switch covers, display covers, heat control panels, instrument panels, center clusters, center panels, room lamp lenses, various display devices such as head-up displays, protective parts, and light-transmitting parts.
Claims
1. A polycarbonate resin composition comprising 1 to 99 parts by weight (component A) of a copolymeric polycarbonate resin in which the content of repeating units (a) represented by the following formula (1) is 5 to 95 mol % and the content of repeating units (b) represented by the following formula (2) is 95 to 5 mol % relative to the total repeating units, and 99 to 1 part by weight of an aromatic polycarbonate resin (component B). 【Chemistry 1】 (In the above formula (1), ring Z is a naphthalene ring, R 1 and R 2 each independently represents at least one group selected from the group consisting of a hydrogen atom, a halogen atom, an alkyl group having 1 to 18 carbon atoms, an alkoxy group having 1 to 18 carbon atoms, a cycloalkyl group having 6 to 20 carbon atoms, a cycloalkoxy group having 6 to 20 carbon atoms, an alkenyl group having 2 to 10 carbon atoms, an aryl group having 6 to 14 carbon atoms, an aryloxy group having 6 to 14 carbon atoms, an aralkyl group having 7 to 20 carbon atoms, an aralkyloxy group having 7 to 20 carbon atoms, a nitro group, an aldehyde group, a cyano group, and a carboxyl group. 【Chemistry 2】 (In the above formula (2), R 3 and R 4 each independently represents at least one group selected from the group consisting of a hydrogen atom, a halogen atom, an alkyl group having 1 to 18 carbon atoms, an alkoxy group having 1 to 18 carbon atoms, a cycloalkyl group having 6 to 20 carbon atoms, a cycloalkoxy group having 6 to 20 carbon atoms, an alkenyl group having 2 to 10 carbon atoms, an aryl group having 6 to 14 carbon atoms, an aryloxy group having 6 to 14 carbon atoms, an aralkyl group having 7 to 20 carbon atoms, an aralkyloxy group having 7 to 20 carbon atoms, a nitro group, an aldehyde group, a cyano group, and a carboxyl group, and when there are a plurality of each of these groups, they may be the same or different, e and f each represent an integer of 1 to 4, and W represents a single bond or at least one group selected from the group consisting of groups represented by the following formula (3): 【Chemistry 3】 (In the above formula (3), R 5 , R 6 , R 7 , R 8 , R 9 , R 10 , R 11 and R 12 each independently represents at least one group selected from the group consisting of a hydrogen atom, an alkyl group having 1 to 18 carbon atoms, an aryl group having 6 to 14 carbon atoms, and an aralkyl group having 7 to 20 carbon atoms, and when there are a plurality of groups, they may be the same or different; R 13 and R 14 each independently represents at least one group selected from the group consisting of a hydrogen atom, a halogen atom, an alkyl group having 1 to 18 carbon atoms, an alkoxy group having 1 to 18 carbon atoms, a cycloalkyl group having 6 to 20 carbon atoms, a cycloalkoxy group having 6 to 20 carbon atoms, an alkenyl group having 2 to 10 carbon atoms, an aryl group having 6 to 14 carbon atoms, an aryloxy group having 6 to 14 carbon atoms, an aralkyl group having 7 to 20 carbon atoms, an aralkyloxy group having 7 to 20 carbon atoms, a nitro group, an aldehyde group, a cyano group, and a carboxyl group; R 15 , R 16 , R 17 and R 18 each independently represents at least one group selected from the group consisting of an alkyl group having 1 to 18 carbon atoms, a cycloalkyl group having 6 to 20 carbon atoms, an alkenyl group having 2 to 10 carbon atoms, an aryl group having 6 to 14 carbon atoms, and an aralkyl group having 7 to 20 carbon atoms, and when there are a plurality of groups, they may be the same or different, c is an integer of 1 to 10, d is an integer of 4 to 7, h and i are integers of 1 to 3, and g is an integer of 1 to 100.
2. 2. The polycarbonate resin composition according to claim 1, wherein the aromatic polycarbonate resin (component B) is an aromatic polycarbonate resin containing a repeating unit derived from bisphenol A.
3. 2. The polycarbonate resin composition according to claim 1, which has a single glass transition temperature.
4. The polycarbonate resin composition according to claim 1, which has a glass transition temperature of 100 to 300°C.
5. Indentation hardness measured according to ISO / TS 19278 is 150 to 400 (N / mm 2 2. The polycarbonate resin composition according to claim 1, wherein
6. 2. The polycarbonate resin composition according to claim 1, which has a pencil hardness of H or more as measured in accordance with JIS K5600.
7. 2. The polycarbonate resin composition according to claim 1, wherein a test piece having a thickness of 2 mm has a total light transmittance of 85% or more.
8. Notched Charpy impact value is 3 kJ / m 2 The polycarbonate resin composition according to claim 1,
9. A molded article obtained by injection molding the polycarbonate resin composition according to any one of claims 1 to 8.
10. A sheet or film obtained by extrusion molding the polycarbonate resin composition according to any one of claims 1 to 8.
Citation Information
Patent Citations
Denwayobidashisochi
JP1976073803A
Polycarbonate polymer having excellent surface hardness
JP1989069625A
Aromatic copolycarbonate
JP1996034846A
Copolycarbonate, copolycarbonate composition and production thereof
JP1996183852A
Optical disk substrate and optical disk
JP2002117580A
Cited By
Polycarbonate resin and molded articles made therefrom
JP7904322B2
Polycarbonate resin and molded article formed of same
JPWO2024090157A1